Pemberdayaan Masyarakat Terkait dengan Pentingnya Pemahaman Hak Atas Tanah di Desa Bayur Kota Samarinda - Deva Vira Ariani; Muhammad Fajar Aulia Fachrendy; Aisyah Rohmah; Poppilea Erwinta (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Land is a source of livelihood and subsistence for people and communities, and is considered the most basic human need due to its high value and usefulness in human life. In fact, land and people are closely intertwined. This underscores the importance of land ownership status. However, there are still individuals who are unaware of permanent land rights, such as Hak Milik, Hak Guna Bangunan, Hak Guna Usaha, and Hak Pakai. This research entitled “Community Legal Awareness of the Importance of Understanding Land Rights in Bayur Village, Samarinda City” uses empirical juridical methods and is accompanied by community service through socialization to the community. The aim is to provide explanations and discussions so that Bayur Village residents understand the importance of the ownership status of land rights for their owners, which can be used as a place to live and productive land that is beneficial to the community in Bayur Village. Through legal counseling, PKM activities have been able to increase community awareness and knowledge regarding the importance of understanding land rights in order to prevent disputes over land owned by the community.